GE_GERICHTE P/16904/2020 vom 8. Februar 2023 - GE Cour de justice (2023)
ORDONNANCE PÉNALE;OPPOSITION TARDIVE;NOTIFICATION PAR VOIE OFFICIELLE;NOTIFICATION IRRÉGULIÈRE;EFFET | CPP.354; CPP.88; CPP.356.al2